2021
DOI: 10.3367/ufne.2021.02.038946
|View full text |Cite
|
Sign up to set email alerts
|

Andrei Sakharov’s research work and modern physics

Abstract: We follow the work carried out by Andrei Sakharov in both research and engineering, from the first domestic thermonuclear charges to fundamental physics. We emphasize the current status of the research fields recognized to have originated in Sakharov’s work: controlled fusion, magnetic cumulation and magnetic explosion generators, induced gravity, cosmological ‘Sakharov’ (baryonic acoustic) oscillations, and baryon asymmetry of the Universe. Another subject that unexpectedly gained momentum in the 21st century… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 130 publications
0
5
0
Order By: Relevance
“…The idea that the action of the gravitational field stems from dynamics of the matter in a curved spacetime was formulated by Sakharov as early as in 1967 (see reprints [43,44] of his 1967 work). This idea is often referred as "induced gravity" [45][46][47]. In a closely related concept of "emergent gravity", gravitational field arises along with spacetime itself from some more fundamental constructs [15,[48][49][50][51].…”
Section: Possible Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea that the action of the gravitational field stems from dynamics of the matter in a curved spacetime was formulated by Sakharov as early as in 1967 (see reprints [43,44] of his 1967 work). This idea is often referred as "induced gravity" [45][46][47]. In a closely related concept of "emergent gravity", gravitational field arises along with spacetime itself from some more fundamental constructs [15,[48][49][50][51].…”
Section: Possible Implicationsmentioning
confidence: 99%
“…In a closely related concept of "emergent gravity", gravitational field arises along with spacetime itself from some more fundamental constructs [15,[48][49][50][51]. Calculations by many research groups showed that the induced gravity appears even in the approximation of non-interacting quantum fields, from a diagram containing only one loop [45][46][47][52][53][54][55]. However, a much more complicated diagram shown in Fig.…”
Section: Possible Implicationsmentioning
confidence: 99%
“…However, Sakharov has not given a detailed description of this transition. As mentioned in [6], later his idea became popular. It was actively discussed in 1990s (see, for example, [7] and references therein).…”
Section: Not By An External Power But By the Truth Itselfmentioning
confidence: 99%
“…These formulas, rooted in nuclear physics, thermodynamics, and hydrodynamics, provide a mathematical framework crucial for understanding the delicate balance that maintains a star's stability and propels its evolutionary trajectory. Over the decades, astrophysicists have diligently constructed and refined these differential equations, drawing inspiration from observational data and theoretical advancements (Altshuler, 2021;Hodson & Wong, 2014;Kaltenborn, 2023;Penprase & Penprase, 2017;Roychoudhuri, 2011). This continuous pursuit of knowledge, aptly represented by the triangle principle (observations-theory-interpretation), has led to remarkable breakthroughs in understanding stellar phenomena.…”
Section: Introductionmentioning
confidence: 99%